THE ROLE OF PERCEIVED ENJOYMENT IN MEDIATING THE INFLUENCE OF INTERACTIVITY, ATTRACTIVENESS, AND SOCIAL PRESENCE ON IMPULSIVE BUYING IN TIKTOK LIVE STREAMING (CASE STUDY ON BATIK NAWILIS) - Rosada, Maisya; Widyastuti, Umi; Berutu, Meta Bara (Yayasan Education and Social Center, 2026)
Driven by the rapid growth of live streaming commerce in Indonesia, this study investigates the psychological mechanisms underlying impulsive buying behavior within the TikTok Live ecosystem. Specifically, this research examines the effects of interactivity, attractiveness, and social presence on impulsive buying, with perceived enjoyment serving as a mediating variable, using batik Nawilis live streaming as the empirical context. This study adopts a quantitative approach using a survey method. Data were collected from 200 respondents in Indonesia who met the criteria of being aged 18–28 years, actively using TikTok live streaming, having watched or interacted with batik Nawilis live streams, and having purchased batik Nawilis products through TikTok live streaming. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings reveal that interactivity, attractiveness, and social presence have positive and significant effects on perceived enjoyment. Furthermore, perceived enjoyment positively and significantly influences impulsive buying. Additionally, interactivity, attractiveness, and social presence indirectly affect impulsive buying through perceived enjoyment as a mediating variable.